Case Report: COVID-19 exacerbates acute lower limb ischemia in patients with popliteal artery entrapment syndrome - Bo, Li; Xiaojiong, Du (Frontiers in Cardiovascular Medicine, 2024)
Non-traumatic lower limb ischemic diseases are extremely rare among young people. Clinically, it is mainly seen in popliteal artery entrapment syndrome (PAES).In addition, with the prevalence of COVID-19 infection, more and more studies report that COVID-19 infection may lead to arteriovenous thrombosis, which could cause lower limb ischemia. This case reported that a 31-year-old male amateur football player developed intermittent claudication after recovering from COVID-19. And, after two months of consultation, he was ultimately diagnosed with PAES. As is well known, PAES is mostly caused by long-term compression of the popliteal artery by abnormal anatomical structures, resulting in thickening of the vascular outer membrane, progression of the disease until intimal damage and thrombosis, leading to lower limb ischemia. During the progression of the disease, there may be multiple factors that accelerate the progression of the disease. Therefore, combined with the patient's clinic history and the related studies on the confirmed thrombosis caused by COVID-19, we can infer that COVID-19 could accelerates the occurrence of PAES.